Adolescence as the Context for Understanding Young Mothers' Engagement with Health Promotion: A Phenomenological Exploration - Catherine Ellis; Peter Sidebotham (MDPI AG, 2023)
Background: The current social construction of young mothers is generally negative, pointing to a lack of engagement with universal services and poor outcomes for their infants and children. However, qualitative studies offer an alternative, more positive construct of young motherhood. Understanding the context of young motherhood can improve the relevance and efficacy of health promotion directed to this group of high-risk mothers. Aim: To explore the lived experience of young women transitioning to motherhood to better understand their experiences and perspective; and what influences their engagement with health promotion aimed to support safer parenting practices and whether their behaviour changes over time with exposure to parenting health promotion. Method: Longitudinal Interpretative Phenomenological Analysis (IPA) was used with five first-time mothers identified with characteristics known to influence poorer outcomes for infants and children such as low educational achievement and economic disadvantage. Participants aged 16 to 19 years were recruited antenatally. Serial in-depth interviews were conducted at three time points during the ante- and post-natal periods. Interviews were transcribed and data were analysed inductively following the prescribed method of double hermeneutic analysis for IPA. Finding: Three themes were identified from the full study: Transition, Information, and Fractured application; the focus of this paper is Transition. Transition revealed that becoming mothers impacted key adolescent developmental tasks; their identity and relationships were significantly affected, both positively and negatively and adolescent brain development influenced behaviour and decision making capability. Adolescence influenced how these young mothers engaged with and interpreted parenting health promotion messages. Conclusions: Young mothers in this study operate within the context of adolescence. Adolescence impacts participants' decision making activity and early parenting behaviours which informs the debate on why young mothers may fail to reduce risks for their infants. This insight can contribute to the development of more effective health promotion/educational strategies, and support professionals to better engage with this high-risk group to improve early parenting behaviour and subsequently improve outcomes for their infants and children.